2015
DOI: 10.1007/s13201-015-0338-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride occurrence in the groundwater in a coastal region of Andhra Pradesh, India

Abstract: Fluoride (F -) content varies from 0.60 to 1.80 mg/L in the coastal region between Chirala and Ongole of Andhra Pradesh, India. It exceeds the threshold limit of 1.20 mg/L in 20 % of the total groundwater samples. The aim of the present study is to assess the controlling factors of F -content. The study area experiences a dry climate and is underlain by Charnockite Group of rocks over which the river and coastal alluvium occur. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…The first case of fluorosis was reported in Prakasam district of Andhra Pradesh (Fig. 2) by Shortt et al (1937). However, the effect of fluoride contamination in India is most profound in the state of Rajasthan (Fig.…”
Section: Indiamentioning
confidence: 99%
“…The first case of fluorosis was reported in Prakasam district of Andhra Pradesh (Fig. 2) by Shortt et al (1937). However, the effect of fluoride contamination in India is most profound in the state of Rajasthan (Fig.…”
Section: Indiamentioning
confidence: 99%
“…Similar investigations using the Gibbs diagram such as Adimalla et al (2018a) have found that elevated concentrations of fluoride are associated with groundwater that plots in the "rock dominance" field in a Gibbs diagram. Similarly, observations were noticed in Kolar and Tumkur Districts of Karnataka (Mamatha and Rao 2010), Chirala and Ongole of Andhra Pradesh (Subba Rao et al 2015;Rao et al 2017), and Chimakurthy pluton, Prakasam District, Andhra Pradesh (Reddy et al 2016). However, it is also supported by the existing negative correlation between fluoride and nitrate (Fig.…”
Section: Mechanism Of Rock Dominancementioning
confidence: 57%
“…Moreover, 34% of groundwater samples are found under Na + -HCO 3 − or mixed type (Na + -K + -HCO 3 − ) and cause favor to fluoride dissolution in the study region. A number of previous studies suggested that the Na + -HCO 3 − water type, decreasing calcium concentration, increasing sodium concentration, and neutral-to-alkaline pH nature of water are more favorable for fluoride dissolution process, thereby accelerating the fluoride concentration in groundwater (Rao et al 2017;Ali et al 2016;Adimalla et al 2018a, b;Narsimha and Sudarshan 2017b). Moreover, Na + -HCO 3 − water type, mainly deeper groundwater, is influenced by the ion exchange process (Saxena and Ahmed 2003).…”
Section: Groundwater Typesmentioning
confidence: 99%
See 2 more Smart Citations